Automation of waste collection using IoT - J, Rajashekar Reddy; J , Mohana (International Journal of Psychosocial Rehabilitation, 2020)
Due to the increased population rate, the urban area is more polluted than the village. Garbage collection is a very challenging task in this current scenario. Most of the dustbins contain a large amount of waste dumped over their capacity level. Finally, the particular place becomes a dirty place. The main aim of this proposed system is to maintain cleanliness in our surroundings. This garbage collection system will reduce overflow of waste from the dustbin using current communication technology concepts. In this system, ultrasonic sensors are used to find the level of garbage in the dustbin. If the garbage level is higher than the set point level, the particular LED bulb will glow, and the alert message will also be sent to the concerned members using GSM and GPS technology.